Finnsheep and their utilization experiences in temperate conditions - Baker, R. L. (Agricultural and Food Science, 1988)
The highly prolific Finnsheep (F) has been exported to more than 40 countries around the world to improve the reproductive performance of local breeds through crossbreeding. The infusion of one-half F into local breeds results in a substantial improvement in all reproductive traits with net reproduction (lambs weaned/ewe mated) being increased by about 25 % in the British Isles and Western Europe and by up to 70—100 % in New Zealand, South Africa and the USA. Heterosis for litter size at birth has been low or negligible in a number of crossbreeding studies involving F. Serious reservations have been expressed about the growth, fleece producton and carcass characteristics of F. While F-cross lambs are usually lighter at birth than local breeds, their weaning and post-weaning weights are often very similar, at least partly due to heterosis. Despite the perceived poor live conformation of purebred F, the carcass weight, quality and composition of F-crosses have been very similar to local breeds or crosses. A striking feature of F-cross carcasses is that they have more kidney and less subcutaneous fat than local breeds. This may be a desirable feature of F-cross in extensive, pastoral farming situations to help sheep survive during droughts or periods of low pasture production. The fleece weight of the purebred F is 30—40 % lower than most local breeds, particularly long-wooled breeds. However, the 1/4-F crosses have consistently been only 5—10 % lower in fleece weight. Studies have reported comparable, or superior, processing qualities of F-cross wool. F-cross ewes have generally been shown to have superior longevity, overall productivity and economic efficiency than local breeds across a diverse range of environments and farming systems. Some of the problems of integrating a highly prolific genotype into extensive, low cost, sheep production systems are discussed. F has been utilized in many countries by producing a new synthetic population containing a certain proportion (1/8 to 1/2) of F ancestry. This approach is usually superior to other crossbreeding options such as stratified crossing or rotational crossing systems.